Validity and utility of the Japanese version of the brief unhelpful thoughts and beliefs about stuttering scale: UTBAS-6-J - Tomisato, Shuta; Yada, Yasuto; Wasano, Koichiro; Kono, Takeyuki; Ozawa, Hiroyuki (Frontiers in Psychology, 2024)
Do adults who stutter have abnormally high social anxiety? Is it related to maladaptive cognition? As these are persistent, unresolved questions in stuttering research, it behooves clinicians to at least assess and attempt to identify social anxiety in patients who stutter and its basis before decisions are made about stuttering treatment. The Unhelpful Thoughts and Beliefs About Stuttering (UTBAS) scale is a self-administered questionnaire that measures the degree of non-adaptive cognition in people who stutter (PWS) due to social anxiety. The 66-item UTBAS is time-consuming to complete, prompting the development of a shorter 6-item version, the UTBAS-6, which is in English. Here, we aimed to assess some psychometric properties of the Japanese version of the UTBAS-6, the UTBAS-6-J, which has not been done to date. In 56 adult patients (mean 32.6 ± 11.1 years) who stutter, we quantified the reliability, the internal consistency, and the concurrent validity of the UTBAS-6-J.